Barriers to the Uptake of Cataract Surgery and Eye Care After Community Outreach Screening in Takeo Province, Cambodia. Issue 3 (May 2017) - Ormsby, Gail M.; Mörchen, Manfred; Fotis, Kathy; Skiba, Dawn Grant; Chim, Channeang; Keeffe, Jill E.
Abstract : Purpose: : To assess the barriers influencing eye healthcare seeking be‐havior after community outreach screening. Design: : A concurrent mixed methods study. Methods: : A total of 469 patients screened during the previous 12 months were followed up, of which 354 (75%) from 5 districts were in‐terviewed in person, using a semi‐structured questionnaire, in‐depth in‐terviews (n = 11), and 16 focus groups (n = 71). SPSS and NVivo were used to analyze response frequency and identify themes. Results: : Of the respondents, 98% (350/354) reported they were told they had an eye problem, with 295 individuals (83%) told to attend CARITAS Takeo Eye Hospital (CTEH) and 55 to have their eyes checked at Kiri Vong Vision Centre. Of those 68.9% (244/354) who reported seeking treatment, only 7.4% (18/244) reported they attended CTEH, 54% (n = 132) attended a "local pharmacy, " 31.6% (n = 77) "self‐treated at home, " 11% (n = 27) reported "using steam from boiling rice, " and 10.7% (n = 26) attended a "traditional healer." Of those who reported reasons for "not attending, " responses included "no time" (47.8%, 86/180), "no one to accompany" (21.7%, n = 39), "fear of losing sight" (17.8%, n = 32), "cannot afford to travel" (16.1%, n = 29), and "eye problem is not serious enough" (15.6%, n = 28). Follow‐up of patient records identified that 128 individuals (79 females) attended eye care services. Conclusions: : Socioeconomic factors, personal concerns, and the use of local cultural remedies were reasons for not seeking eye hospital treatment. An integrated community approach to improve awareness and uptake of appropriate treatment is recommended.